The rearing system modulates biochemical and histological differences in loin and ham muscles between Basque and Large White pigs. (6th September 2020) - Lefaucheur, L.; Lebret, B.
Abstract : Conventional pork production, based on highly selected breeds for growth efficiency and carcass leanness, is generally considered to decrease pork quality. In contrast, non-selected breeds produced in extensive systems are associated with high pork quality, which is generally attributed to higher intramuscular fat (IMF ) content and less glycolytic muscle metabolism. The present study aimed to determine biochemical, histological and quality traits of loin and ham muscles of pigs from selected Large White (LW ) and local French, non-selected Basque (B ) breeds. Pigs were reared in a conventional indoor (C, slatted floor), alternative (A, indoor bedding and outdoor area) or extensive system (E, free range, B pigs only). A total of 100 castrated males were produced in 2 replicates, each containing 5 groups of 10 pigs based on breed and system: LWC, LWA, BC, BA and BE. The glycolytic longissimus muscle (LM ) and semimembranosus muscle (SM ), and the deep red (RSTM) and superficial white (WSTM) portions of semitendinosus muscle (STM ) were studied at 145 kg BW. Overall, breed induced stronger effects on muscle traits than the rearing system, among which the E system induced greater changes. The lower muscle growth of B pigs was associated with fewer muscle fibers and a smaller cross-sectional area (CSA ) of glycolytic fibers ( P < 0.01). The SM was less glycolytic and more oxidative in B than in LW pigs ( P < 0.001). The WSTM followed a similar trend, with a larger relative area of type I fibers in B pigs. In contrast, the LM and RSTM were more oxidative in LW pigs. B pigs had higher IMF content and ultimate pH in all muscles, along with lower glycolytic potential, less light and redder meat in the LM and SM ( P < 0.001). Compared to the C system, the A system induced only a shift towards a more oxidative metabolism in the LM and a smaller fiber CSA in the RSTM of LW pigs ( P < 0.05), without influencing pork quality traits. Compared to BC pigs, BE pigs had a more oxidative and less glycolytic muscle metabolism, along with higher ultimate pH, lower lightness and redder meat ( P < 0.01), but similar IMF content. Overall, results indicate that influences of breed and rearing system on muscle properties depend on muscle type, and that IMF content and fiber-type composition are unrelated traits that can be modified independently by genetic or rearing factors.